The hypotensive action of nitroprusside. therapeutic Applications - Monge Cassinelli, Carlos (1956)
Page and colleagues have demonstrated the utility of sodium nitroprusside as a hypotensive and pointed out some of its pharmacological characteristics. Sodium nitroprusside, [(Na2 CcN Fe) 5 (NO)] (2H20), is slowly decomposed in the body with cyanogen production. It seems that the existing sulfídridos groups in some tissues act in this decomposition and reaction type enzyme is not.